2017
DOI: 10.1126/science.aah7124
|View full text |Cite
|
Sign up to set email alerts
|

Hidden dynamics in the unfolding of individual bacteriorhodopsin proteins

Abstract: Protein folding occurs as a set of transitions between structural states within an energy landscape. An oversimplified view of the folding process emerges when transiently populated states are undetected because of limited instrumental resolution. Using force spectroscopy optimized for 1-μs resolution, we reexamined the unfolding of individual bacteriorhodopsin molecules in native lipid bilayers. The experimental data reveal the unfolding pathway in unprecedented detail. Numerous newly detected intermediates—m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
219
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(225 citation statements)
references
References 48 publications
(111 reference statements)
6
219
0
Order By: Relevance
“…Protein-membrane interactions play pivotal roles in numerous biological processes, including membrane protein folding (Yu et al, 2017;Popot and Engelman, 2016;Min et al, 2015), lipid metabolism and transport (Giordano et al, 2013;Reinisch and De Camilli, 2016;Hammond and Balla, 2015;Wong et al, 2017), membrane trafficking (Zhou et al, 2017;Pérez-Lara et al, 2016;Wu et al, 2017;Hurley, 2006;Shen et al, 2012;McMahon and Gallop, 2005), signal transduction (Dong et al, 2017;Aggarwal and Ha, 2016;Lemmon, 2008;Das et al, 2015), and cell motility (Wang and Ha, 2013;Tsujita and Itoh, 2015). Studying these interactions is often difficult, especially when they involve multiple intermediates, multiple ligands, mechanical force, large energy changes, or protein aggregation (Dong et al, 2017;Pérez-Lara et al, 2016;Arauz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Protein-membrane interactions play pivotal roles in numerous biological processes, including membrane protein folding (Yu et al, 2017;Popot and Engelman, 2016;Min et al, 2015), lipid metabolism and transport (Giordano et al, 2013;Reinisch and De Camilli, 2016;Hammond and Balla, 2015;Wong et al, 2017), membrane trafficking (Zhou et al, 2017;Pérez-Lara et al, 2016;Wu et al, 2017;Hurley, 2006;Shen et al, 2012;McMahon and Gallop, 2005), signal transduction (Dong et al, 2017;Aggarwal and Ha, 2016;Lemmon, 2008;Das et al, 2015), and cell motility (Wang and Ha, 2013;Tsujita and Itoh, 2015). Studying these interactions is often difficult, especially when they involve multiple intermediates, multiple ligands, mechanical force, large energy changes, or protein aggregation (Dong et al, 2017;Pérez-Lara et al, 2016;Arauz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that using a long AFM tip probe whose cantilever was far away from the cell surface can effectively improve the spatial resolution of AFM images. 52 Besides, shortening the length of he cantilever can reduce viscous damping, and removing reflective gold layers from the cantilevers can reduce thermal drift and increase force sensitivity, 152,157 leading to the smaller response times of the AFM probe. Hence, fabricating adequate AFM probes can potentially benefit the improvement of AFM imaging resolution.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…During the retraction process of the AFM tip, the transmembrane protein is sequentially unfolded, which results in sawtooth-like peaks in the force curve, 152 as shown in Fig. 7(d).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In single-molecule force spectroscopy, for example, the extension x(t) of a protein or DNA can be monitored with microsecond time resolution, enabling observation of fast conformational fluctuations. The information contained in a trajectory x(t) can be used to develop more accurate dynamical models that go beyond phenomenological theories commonly employed to describe transition rates.…”
mentioning
confidence: 99%